Occurrence of gastrointestinal parasitic infection in bovines of Haryana - BHANOT, VANDNA; YADAV, RAHUL; KUMAR, PANKAJ; PRAKASH, ANAND (The Indian Journal of Animal Sciences, 2023)
Gastrointestinal (GI) parasitic infections are the major constraint for livestock production causing huge economiclosses to the livestock producers in terms of decreased milk production and reduced weight gain. Gastrointestinaldisorders including diarrhoea may be caused by various etiological factors but parasitic infections play a significantrole. A total of 1755 faecal samples from cattle (n = 594) and buffaloes (n = 1161) with the history of digestive disturbances/disorders were tested at four Disease Investigation Laboratories at Ambala, Bhiwani, Mahendergarhand Rohtak in Haryana during July 2020 to June 2021. All the faecal samples were processed by floatation and sedimentation methods. Coprological examination revealed 33.5% cattle and 37.3% buffalo as positive for GIparasites. The major parasitic infection of Amphistomes (6.3%), Buxtonella sulcata (14.8%) and Strongyles (11.05%)was observed in bovines. Highest infection of Strongyles (13.3%) and Buxtonella sulcata (17.4%) was found in cattle and buffaloes, respectively. Gastrointestinal parasitic infections in calves were in higher frequency than adult animals. Season-wise GI parasitic infections were recorded to be non-significantly higher in rainy season. Area-wiseoccurrence of parasitic infection was recorded highest in Rohtak followed by Bhiwani, Ambala and the least in Mahendergarh district of Haryana. This kind of study is found to be helpful in formulating effective control trategiesagainst GI parasitic infections on regional basis.